Novel approach to identify phenoloxidases inhibitors: Optimization of spectrophotometric MBTH assay for high throughput use enzymatic assays and analysis. (November 2018) - Zeyer, Estelle; Heuson, Egon; Himber, Charlotte; Phalip, Vincent; Le Bris, Cédric; Dhulster, Pascal; Brisabois, Anne; Flahaut, Christophe; Cudennec, Benoit; Grard, Thierry; Duflos, Guillaume
Abstract: This study presents a miniaturized 3-methyl-2-benzothiazolinone hydrazone hydrochloride-assay (MBTH-assay) 1, optimized for high-throughput measurement of shrimp phenol oxidase activities and the screening of potential inhibitors of post-mortem melanosis. To validate this approach, assay parameters, including limit of detection and dynamic range, were compared to values obtained for DOPAchrome-assay, used here as a reference method. A reliable high-throughput automatized analysis was also performed, under standardized parameters, in order to compare and characterize 40 potential inhibitors of phenol oxidase activities. Among the selected molecules, twenty showed inhibitory action. Enzyme-inhibitor dissociation constant (Ki ), median inhibitor concentration (IC50 ) and inhibition modes could be determined for nine of them. 4-Hexylresorcinol, n -phenylthioureal -cystein and glutathione displayed Ki values lower than sulfite salts (Na2 S2 O5 and Na2 SO3 ) used as positive controls. Graphical abstract: Highlights: Miniaturized MBTH-assay for phenol oxidases detection. High throughput screening assay for rapid selection of phenol oxidases inhibitors. Comparison of inhibitory actions under standardized conditions. Application to post mortem melanosis inhibition in Penaeus monodon shrimp.